2003
DOI: 10.5144/0256-4947.2003.20
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Levels in Drinking Water in the Central Province of Saudi Arabia

Abstract: Background: This study was designed to assess the fluoride levels in drinking water in the Central Province of Saudi Arabia. Materials and Methods: A total of 817 water samples were collected from 260 locations in Central Saudi Arabia. An atomic absorption spectrophotometer [HACH instrument, model DR 3000] was used in the analyses of water samples for fluoride levels. Results:The results showed that fluoride levels vary between 0.00 and 6.20 ppm. About 75% and 6% of the population in Riyadh and Qassim regions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
0
21
1
Order By: Relevance
“…0.00.3ppm and Riyadh, so that the DMFT score has apparently more than tripled in Riyadh since 1991. The DMFT was also much higher as compared with a mean DMFT of 2.67 reported by Al-Shammery 2 in 1999 for 12 13-year-old Saudi schoolchildren. Almas et al 17 reported a mean DMFT score of 2.58 and 2.64 respectively among selected urban and rural 12-year-old schoolchildren in Qaseem.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…0.00.3ppm and Riyadh, so that the DMFT score has apparently more than tripled in Riyadh since 1991. The DMFT was also much higher as compared with a mean DMFT of 2.67 reported by Al-Shammery 2 in 1999 for 12 13-year-old Saudi schoolchildren. Almas et al 17 reported a mean DMFT score of 2.58 and 2.64 respectively among selected urban and rural 12-year-old schoolchildren in Qaseem.…”
Section: Discussioncontrasting
confidence: 51%
“…The zones with similar levels of water fluoride concentrations were identified utilising a map prepared from the water analysis study 12 . The list of these zones was considered as a sampling frame for the subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water supply in Riyadh is based mainly on natural ground water and/or desalination water. The fluoride (F) concentration was determined to be between 0·00 and 2·5 mg/L [33,34]. Assuming a mean value of 0·7 mg F/L [34], the mean weight of fluoride ingested from drinking water and soft and fruit drinks would have been 1·18 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…This increase was quite stable with reference to population growth. However, the large consumption of bottled drinking water per person was mainly due to low level of fluoride concentration (Mohamed and Abdel Fattah 1987;AlDosary et al 2003) and apprehension about the contaminants of communal drinking water, fewer impurities, better taste, and possibly conferring higher social status (Wigle et al 1986;Paul et al 1998).…”
Section: Introductionmentioning
confidence: 97%